2023
DOI: 10.37616/2212-5043.1341
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for chylothorax after pediatric heart surgeries: retrospective analysis of a large institution database​

​Muhammad Shahzad,
Yasser abdulrhman Alheraish,
​​Bushra ​ Algethami
et al.

Abstract: Background: Risk factors for postoperative chylothorax in children who had cardiothoracic procedures are not always clear. Due to complex course in post-operative care, It’s always challenging to find the risk factors, and their management. Objective: The aim of our study was to identify the incidence, risk factors and effective treatment approaches for chylothorax after pediatric heart surgery. Methods: Children who had the cardiac surgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Other related literature reported that the Risk Adjustment for Congenital Heart Surgery (RACHS-1) method was used to score the surgical approach to investigate its effect on postoperative chylothorax. 29 Some studies have shown that the complexity of surgery is a major risk factor for chyle emulsion. The higher the RACHS-1 score is, the higher the complexity of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Other related literature reported that the Risk Adjustment for Congenital Heart Surgery (RACHS-1) method was used to score the surgical approach to investigate its effect on postoperative chylothorax. 29 Some studies have shown that the complexity of surgery is a major risk factor for chyle emulsion. The higher the RACHS-1 score is, the higher the complexity of surgery.…”
Section: Discussionmentioning
confidence: 99%